Perancangan Media Promosi Dilon Coffee & Eatery Dengan Teknik Hand Lettering Sebagai Upaya Mengenalkan Kepada Masyarakat - Helmi, M Alfiyan; Budiardjo, Hardman; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of designing a media campaign Dilon coffee & eatery This is to introduce to the public. The research was conducted using qualitative research method is to conduct interviews, observation, documentation, and literature to get the data used to support the drafting of a media campaign design. Data were analyzed using multiple stages, namely data reduction, data presentation and conclusion. From the data analysis found some keywords that refer to promotional media communication strategy that will be used to achieve the target audiance ditujuh. After analysis of the data, ditemukanlah concept or keyword designing a media campaign called